Attitude Towards Science Among Lower Secondary Students in Johor Bahru - Yee, Leong Sok; Abdul Manap, Yazid (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
The purpose of the study was to investigate attitude towards science among lower secondary students in Johor Bahru. The attitude in this study included interest, perception towards science and motivation. The study was carried out in Johor Bahru, Johor. The study adopted quantitative descriptive research designs and questionnaires were used in the study. A total of 370 respondents constituted the sample of the study, which included Form 2 lower secondary students from Johor Bahru. Data was analysed to obtain frequency, mean and standard deviation. The results revealed that laboratory activity, curiosity to discovery science and science as a tool to understand the world is able to improve science learning. As a conclusion, interest especially created by laboratory activity, perception of student when they are curios to discovery science and motivation factor when students know that science as a tool to understand the world are able to improve students science learning in lower secondary schools in Johor Bahru. The implication was that school teachers could prepare more laboratory activities in science lesson. They also can stimulate students’ curiosity to discovery science and related science knowledge to the world so that students are interested and motivated to learn science. Future studies on this subject would be beneficial to understand more deeply the relationship between student personal factors with science achievement.